2016
DOI: 10.1158/1535-7163.mct-16-0258
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Modeling of KIF5B–RET Fusion Lung Adenocarcinoma

Abstract: RET fusions have been found in lung adenocarcinoma, of which KIF5B-RET is the most prevalent. We established inducible KIF5B-RET transgenic mice and KIF5B-RET-dependent cell lines for preclinical modeling of KIF5B-RET-associated lung adenocarcinoma. Dox-induced CCSP-rtTA/tetO-KIF5B-RET transgenic mice developed invasive lung adenocarcinoma with desmoplastic reaction. Tumors regressed upon suppression of KIF5B-RET expression. By culturing KIF5B-RET-dependent BaF3 (B/KR) cells with increasing concentrations of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 35 publications
0
82
0
Order By: Relevance
“…The drug is active against RET M918T (IC 50 = 4.34 nmol/L), but displayed reduced activity against the gatekeeper mutations RET V804L (IC 50 = 319 nmol/L) and RET V804M (IC 50 = 266 nmol/L; ref. 14) in the biochemical assay. In the same assay, the IC 50 values of RXDX-105 against VEGFR1/FLT and VEGFR2/KDR are 140.60 nmol/L and 257.60 nmol/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The drug is active against RET M918T (IC 50 = 4.34 nmol/L), but displayed reduced activity against the gatekeeper mutations RET V804L (IC 50 = 319 nmol/L) and RET V804M (IC 50 = 266 nmol/L; ref. 14) in the biochemical assay. In the same assay, the IC 50 values of RXDX-105 against VEGFR1/FLT and VEGFR2/KDR are 140.60 nmol/L and 257.60 nmol/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, RXDX-105 was able to inhibit RET M918T, an activating mutation found in the majority of cases of multiple endocrine neoplasia type 2B (35). However, point mutations at V804 site, V804L and V804M, could render the tumor less sensitive to RXDX-105 treatment based on the biochemical activity, but whether this is true in the clinic requires further clinical evidence (14). Inhibition of RET was confirmed in cells by measuring RET pathway phosphorylation, and this correlated with inhibition of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our decision to specifically study resistance to the RET-TKI ponatinib was guided by the low-nanomolar affinity with which ponatinib inhibits the RET kinase domain, its approval for use in patients with CML, as well as the ongoing clinical studies assessing its efficacy in RET-positive NSCLC. Further, a recent study in KIF5B-RET-dependent BaF3 cells demonstrated that the vandetanib-resistant RET G810A mutation exhibited increased sensitivity to ponatinib, concluding that ponatinib is the current “drug of choice” for targeted inhibition of RET in the clinic (42). …”
Section: Discussionmentioning
confidence: 99%
“…As TKIs are being employed in the treatment of other oncogenic drivers such as cabozantinib or vandetanib for RET and entrectinib for NTRK, the emergent resistance mutations are beginning to be reported in the literature. Similar to the ALK situation, the vandetanibmediated KIF5B-RET810A resistance mutation paradoxically enhances its sensitivity to other TKIs, ponatinib and lenvatinib, in vitro (84). Therefore, studying the sensitivity of each gatekeeper mutation to the specific therapeutic agent will guide the management of acquired resistance.…”
Section: Modifications Of the Oncogenic Drivermentioning
confidence: 99%